Developing Educational Game as Language Acquisition Media for Young Learners - Setyawan, Farid Helmi; Susanto, Sofyan (JET ADI BUANA, 2019)
Language acquisition is the process of language mastery done by children naturally when they learn their mother of tongue. The era of globalization with the presence of sophisticated technology requires children to be able to use technology well. With the presence of technology, it makes it easy for children to learn many things, especially languages. The purpose of using language learning media based on the educational game culture character of the android system is to increase language acquisition for early childhood. With this language learning media, early childhood is helped in understanding and mastering verbal vocabulary. In addition, in this era, many people have Smart Phones that can load various applications. In addition, it is very easy for parents to access or open an android-based media application from their Smart Phones. The research method used is research and development. This development was carried out in the learning media, namely language learning media based on the educational character of the culture system of the android system. This study uses the Borg and Gall development theory which has been simplified into six stages. This research was conducted at PAUD / TK in the Ngawi Regency, East Java. The research subjects are early childhood and parents in PAUD/TK Ngawi Regency with a total of 50 people. The results of this study are in the form of educational learning applications based on the educational game culture character of the Android system. The results of the data analysis showed that, from 50 respondents who are parents of children, 44 people stated that the media ere feasible and very useful and 45 people gave positive responses. From the results of the addition of the acquisition of children's language shows 46 children experienced progress and the addition of the acquisition of a new language. The results of this study are expected to facilitate early childhood in language acquisition